2022
DOI: 10.3390/ijms232113127
|View full text |Cite
|
Sign up to set email alerts
|

NGF and the Male Reproductive System: Potential Clinical Applications in Infertility

Abstract: Infertility is a worldwide health issue defined by the World Health Organization (WHO) as the inability to establish a pregnancy after 12 months or more of regular and unprotected sexual intercourse. Male infertility etiology can be related to either congenital or acquired factors. The therapeutical approach to male infertility depends on the underlying causes and includes medical and surgical treatments. In recent studies, the potential role of nerve growth factor (NGF) in male reproductive physiology has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 250 publications
0
10
0
Order By: Relevance
“…From the point of view of neurological mediators, neurotrophins may play key roles [ 63 – 66 ]. Neurotrophins are active not only on nerve cells but also play a key role as endocrine and paracrine regulators of the cardiovascular, immune and endocrine systems to regulate homeostasis in physiological and/or pathological conditions [ 66 68 ].…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of neurological mediators, neurotrophins may play key roles [ 63 – 66 ]. Neurotrophins are active not only on nerve cells but also play a key role as endocrine and paracrine regulators of the cardiovascular, immune and endocrine systems to regulate homeostasis in physiological and/or pathological conditions [ 66 68 ].…”
Section: Etiologymentioning
confidence: 99%
“…From the point of view of neurological mediators, neurotrophins may play key roles [ 63 – 66 ]. Neurotrophins are active not only on nerve cells but also play a key role as endocrine and paracrine regulators of the cardiovascular, immune and endocrine systems to regulate homeostasis in physiological and/or pathological conditions [ 66 68 ]. Indeed, the brain-derived neurotrophic factor (BDNF) is normally affected under stress conditions [ 69 , 70 ] slightly increased in the serum of individuals with GD compared to the control group, even if in this study, patients with depressive diseases were not excluded which could be the underlying reason for the rise of BDNF [ 71 ].…”
Section: Etiologymentioning
confidence: 99%
“…Girls who start treatment before the age of 6 have better outcomes than patients who start treatment between 6 and 8 years while starting therapy after 8 years of age does not appear to be associated with an increase in height in adulthood [1,11,71]. GnRHa therapy is generally well tolerated in childhood, although the most frequently described adverse events are headache, injection site reactions and hot flushes, which in most cases occur early and are resolved by subsequent GnRHa administrations [11,[78][79][80]. More rare is the occurrence of vaginal discharge, or the development of a sterile abscess at the injection site or at the subcutaneous implant site, which may lead to loss of efficacy of the therapy [3,76].…”
Section: Treatmentmentioning
confidence: 99%
“…The function of neurotrophins is to maintain the survival and differentiation of neurons, but it has also been demonstrated that all known neurotrophins and their receptors are expressed in the testes [25]. In animals, three members of the tyrosine protein kinase receptor (TRK) family are known: TRK-A, which binds to the nerve growth factor (NGF); TRK-B, which binds to the brain-derived neurotrophic factor (BDNF) and neurotrophin-4 (NT-4); and TRK-C, which binds to neurotrophin-3 (NT3) [26].…”
Section: Introductionmentioning
confidence: 99%